PENGAWASAN PEREDARAN KOSMETIK ILEGAL OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) DI KOTA PEKANBARU - Pitri, Adek; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Cosmetic products that do not have a notification or illegal number that is not in accordance with the applicable regulations are still a problem for the people of Pekanbaru. This result can be seen by the fact that there are cosmetic distribution facilities selling illegal cosmetics that have not been controlled by BBPOM in Pekanbaru. The study discusses the controlling of illegal cosmetics circulation by BBPOM in Pekanbaru. The purpose of this study was to find out how the controlling carried out by BBPOM on the circulation of cosmetics in Pekanbaru City. This study uses descriptive qualitative methods. This study uses Stoner, Freeman and Gilbert’s controlling theory with standard setting indicators and performance appraisal methods, performance appraisal, comparing performance with standards, taking corrective actions. The results of the research show that BBPOM’s controlling of the circulation of illegal cosmetics products in Pekanbaru has not been effective due to the lack of human resources to conduct supervision, the cost of controlling that must be regulated or planned and the participation of the public in controlling is still lacking. Therefore, in order for controlling to be effective it is necessary to increase the number of employees, plann costs in controlling and provide guidance to business actors and also to consumers. Keywords: Controlling, Circulation, Cosmetics, Illegal